2012
DOI: 10.1007/s10162-012-0350-3
|View full text |Cite
|
Sign up to set email alerts
|

Temporal-Envelope Reconstruction for Hearing-Impaired Listeners

Abstract: Recent studies suggest that normal-hearing listeners maintain robust speech intelligibility despite severe degradations of amplitude-modulation (AM) cues, by using temporal-envelope information recovered from broadband frequency-modulation (FM) speech cues at the output of cochlear filters. This study aimed to assess whether cochlear damage affects this capacity to reconstruct temporal-envelope information from FM. This was achieved by measuring the ability of 40 normalhearing listeners and 41 listeners with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
1
9
1
Order By: Relevance
“…Consistent with other studies (Gilbert and Lorenzi, 2006;Swaminathan, 2010;Lorenzi et al, 2012;Swaminathan et al, 2014;L eger et al, 2015), our results suggest that the reception of TFS speech is based on the use of RENVs for both NH and HI listeners. In the current study, the reception of one-band and four-band TFS speech was compared to speech signals created through the extraction of 40 bands of ENVs from each type of TFS speech.…”
Section: Role Of Renvs In Perception Of Tfs Speechsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with other studies (Gilbert and Lorenzi, 2006;Swaminathan, 2010;Lorenzi et al, 2012;Swaminathan et al, 2014;L eger et al, 2015), our results suggest that the reception of TFS speech is based on the use of RENVs for both NH and HI listeners. In the current study, the reception of one-band and four-band TFS speech was compared to speech signals created through the extraction of 40 bands of ENVs from each type of TFS speech.…”
Section: Role Of Renvs In Perception Of Tfs Speechsupporting
confidence: 92%
“…One is that ENV recovery from TFS speech was already optimal for the HI listeners and thus the artificial-recovery of the ENVs did not provide any further benefit. Second, it is possible that the RENVs were internally smeared due to the broadened auditory bands associated with cochlear hearing loss and thus led to fewer independent usable ENVs (e.g., Baskent, 2006;Swaminathan and Heinz, 2012;Lorenzi et al, 2012). Third, the RENV cues may have been corrupted by the amplification of noise during the generation of TFS speech (see Apoux et al, 2013).…”
Section: Role Of Renvs In Perception Of Tfs Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…In a modeling study, Heinz and Swaminathan (2009) simulated the broadening of auditory filters that typically occurs with hearing loss and showed that such broadening resulted in a reduction in the degree to which ENV cues can be recovered from TFS speech. Such broadening of peripheral auditory filters could have an effect on the envelope reconstruction from TFS speech (e.g., Heinz and Swaminathan, 2009;Lorenzi et al, 2012). Thus, it was expected that performance would decrease with a reduction in the number of RENV bands.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if the speech processor is mapped with an eight-channel continuous interleaved sampling (CIS) strategy, the bandwidth of the digital filters is approximately three times wider than the bandwidth of the normal auditory filters. Consistent with this prediction, Lorenzi et al (2012) showed that the broadening of cochlear filters typically associated with sensorineural hearing loss has a detrimental effect on the ability to use the AM speech cues recovered from the broadband FM speech cues, when cochlear filters are broadened by a factor greater than two.…”
Section: Introductionmentioning
confidence: 64%